The Marketing Firm and the Consumer Organization: A Comparative Analysis With Special Reference to Charitable Organizations - Foxall, Gordon Robert; Sigurdsson, Valdimar; Gallogly, Joseph K. (Frontiers in Psychology, 2020)
The accurate delineation of various forms of business organization requires a comparative analysis of their objectives, functions, and organizational structures. In particular, this paper highlights differences in managerial work between business firms and non-profits exemplified by the charitable organization. It adopts as its template the theory of the marketing firm, a depiction of the modern corporation as it responds to the imperatives of customer-oriented management, namely consumer discretion and consumer sophistication. It describes in §2 the essentials of the theory and its basis in consumer behavior analysis, and outlines its unique position as the organization responsible for marketing transactions, based on objective exchange, competitive markets and prices, and the deployment of the entire marketing mix. §3 deals in greater depth with the objective, strategic functions, and organization of the marketing firm in terms of the concepts of metacontingency and bilateral contingency. §4 discusses how the marketing firm differs from charities in terms of goal separation, market-based pricing and competition, the entrepreneurial (strategic) process, the pursuit of customer-oriented management, and organizational structure. Particular attention is accorded the organizational differences between marketing firms and charities, which arise as a direct consequence of the distinct patterns of contingency they entail. §5 discusses the implications of the foregoing analysis and draws appropriate conclusions.